(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
There is a paradoxical situation in the developing, Sub Saharan and Asian countries where we are seeing the drastic rise in excess male mortality in developed countries, and excess female mortality, which are emerging with similarly dramatic improvement in our societies’ overall health. It is almost clear that women biologically have certain benefits that allow them to live longer lives. Therefore, women prefer to survive longer than men with fair treatment and diet. In nearly all countries, women have longer life expectancy, while the benefits in terms of disparity in the life expectancy of men and women vary from country to region. There are disparities in mortality between the sexes at the very beginning of life which are free of externality and affect this disparity. The gender genetic disparity is related to a higher susceptibility to biological ageing for women. In addition, feminine hormones and women’s reproductive function have a strong correlation to increased life expectancy.